Role of Percutaneous Bone Marrow Aspirate Injection in Delayed Union of Femur and Tibia Diaphyseal Fractures - Rizwan H. Malik,M. ZeeshanAslam, Ali Shami (Journal of Rawalpindi Medical College, 2018)
Background: To compare the results of percutaneous bone marrow aspirate injection with autologous bone grafting in the treatment of delayed union of femur and tibia diaphyseal fractures using Union Scale Score. Methods: In this randomized controlled trial 88 patients with delayed diaphyseal fracture union of either tibia or femur were divided into two groups of 44 patients each (Group A=bone marrow aspirate injections and Group B=autologous bone graft).The study outcome was assessed in terms of Union Scale Score after 6 weeks interval for 18 weeks time period.In Group A,the skin over iliac crest, about 2-4 cm from anterior superior iliac spine was infiltrated with about 3 ml of 2% plain lignocaine. A bone marrow aspiration needle with multiple distal holes was inserted between the two tables of iliac bone. Twenty ml bone marrow was aspirated. The needle was then replaced with a 16 gauge spinal needle and the BMA was injected in the vicinity of fracture site(non-union) under fluoroscope guidance. The recipient site was then sealed with band aid. In Group B, autogenous iliac bone graft taken by standard technique under general anaesthesia was harvested into the fracture site and immobilized by plaster of Paris cast where indicated. Fracture site mobility, tenderness and radiological features were assessed using the Union Scale Score in which union was considered with a score of 6 or more. In case of non-union, a secondary procedure was performed. Results: At 18 weeks follow-up, 70.4% cases in percutaneous bone marrow group and 93.2% in autologous bone graft group had achieved union scale score of 6 or above, though this difference was significant (p-value, 0.01). Conclusion: Percutaneous bone marrow aspirate injection is an effective alternative to autologous bone grafting for the treatment of delayed union of long bone fractures.